Sex-Specific Physical Activity and Weight Status in German Schoolchildren: Interim Results from the Hand on Heart Study - Meike Schrader; Jennifer Wieprecht; Federico Morassutti Vitale; Simone Katrin Manai; Samar Shamas; Marcel Müller; Maren Baethmann; Anja Tengler; Roxana Riley; Guido Mandilaras; Nikolaus Alexander Haas; Delphina Gomes (Children)
Background/Objectives: physical activity (PA) in children offers lifelong benefits, yet nearly four in five children are insufficiently active. We examined sex-specific differences in sport participation by sport type and its association with weight status. Methods: in the ongoing hand-on-heart-study (“Hand-aufs-Herz”), comprehensive data on sociodemographic profiles, PA, and anthropometry were collected from 922 school-aged children, adolescents, and young adults (8–20 years) in Germany. Sex-specific differences in sport participation, sport types, and weight status were analyzed using descriptive statistics and logistic regression models. Results: based on the eligibility criteria for analysis (ages 8–18 years), 883 pupils were included (mean age 13.1 ± 2.4 years), 406 (46%) were females. Compared to females, males had a 43% higher chance of being members of a sports club and were more likely to spend more days/week on sports (44–85%). Males participated more in football, martial arts, and basketball while females favored gymnastics and volleyball. As age increased, males had a 30% higher likelihood of not being sports club members (females: 13%). Overweight/obese males had twice the risk of lacking sports memberships. The largest body mass index (BMI) difference was found in males and females participating in athletics, with −4.64 kg/m2 (males) and −1.99 kg/m2 (females) compared to their counterparts without club memberships. Conclusions: in conclusion, sports participation should be encouraged especially among females and overweight/obese males. Targeted strategies should focus on promoting inclusive and non-competitive activities that cater to their interests.